To fall for modernity. An essay against the anti-systemic critique - Bielik-Robson, Agata (Journal of Public Governance, 2014)
This essay constitutes an attempt to criticize the so-called anti-systemic critique from the positions which strongly affirm modernity as an epoch based on the primacy of life over thinking. By referring to the ideas of Marshall Bermann which he called “Marxist Vitalism”, this essay emphasizes a unique and innovative role of the concept of life in modernity as opposed to any apriorical and preestablished intellectual project. The seemingly astonishing harmony between the Left and Right variants of “anti-modernism” consists precisely in the fact that all those thinkers who criticize modernity are most of all thinkers who naturally assume the old, premodern, essentially Platonic primacy of thinking over life. In its constructive part, the essay presents the modern idea of a “promised life” which it links to political messianism; it expresses an optimistic belief that it can become a new inspiration for the thinkers to come who will accept the specificity of modernitas and learn how to be loyal to its premises.